Assessment of the accuracy of portable monitors for halitosis evaluation in subjects without malodor complaint. Are they reliable for clinical practice? - Falcão, Denise Pinheiro; Miranda, Priscila Carvalho; Almeida, Tayana Filgueira Galdino; Scalco, Monique Gomes da Silva; Fregni, Felipe; Amorim, Rivadávio Fernandes Batista de (Journal of Applied Oral Science, 2017)
Halitosis is defined as a foul odor emanated from the oral cavity, with great impact in quality of life and social restraints. Recently, the use of Breath Alert™ in research increased significantly. Halimeter™, another portable device, is often used in clinical practice. Nevertheless, not many studies have verified the accuracy and compared the results of both devices simultaneously. Objective: To verify the accuracy of Breath Alert™ and Halimeter™ in patients without chief complaint of halitosis, using the organoleptic test (OT) as "gold standard." The second aim was to verify whether their concomitant use could enhance the diagnostic accuracy of halitosis. Material and Methods: A cross-sectional analytical study was performed. The quality of expired air of 34 subjects without chief complaint of halitosis was assessed. Two experienced examiners carried out the OT. Afterward, a third blinded examiner performed Halimeter™ (HT) and Breath Alert™ (BA) tests. Results: The OT identified halitosis in 21 subjects (62%). The area under the ROC curve (95% confidence interval) was 0.67 (0.48-0.85) and 0.54 (0.34-0.75) for HT and BA, respectively. The accuracy for HT and BA was 59% and 47%, respectively. The combined usage of HT and BA provided 11 positive results, being 9 subjects (43%) out of the total of 21 positive cases. Conclusions: Halimeter™ and Breath Alert™ were not able to diagnose halitosis in non-complainer subjects at the same level as the organoleptic examination, since their accuracy were low. Our results suggest that such portable devices are not reliable tools to assess halitosis and may neglect or misdiagnose a considerable number of patients in clinical practice.